The Association of Dietary Intake of Calcium and Vitamin D to Colorectal Cancer Risk among Iranian Population - Hosseinzadeh, Payam (Asian Pac J Cancer Prev, 2019)
BACKGROUND: Vitamin D and Calcium have a possible protective impact versus rectal neoplasm. Vitamin D, an important nutrient, is vital to regulate the absorption of calcium and bone mineralization; nevertheless, in a case-control study in Iran, we investigated the relationship among the dietary intake of vitamin D and calcium with the hazard of rectal neoplasm. METHODS: 363 subjects (162 cases and 201 controls) participated in the case- control Study from March 2017 to November 2018. Dietary intake of Calcium and Vitamin D was calculated using a 148-items food-frequency questionnaire. RESULTS: Since altering the strong confounding agents, the multivariate risk proportion within the dietary vitamin D intake was OR=0.2, 95%CI 0.1-0.5, P-value <0.001 among cases. There was no association in case of calcium and rectal cancer. CONCLUSIONS: Taken together, a possible reduction in the hazard of rectal neoplasm with dietary intake of Vitamin D within Iranian patients was observed.